Perancangan Buku Komik Tentang Penularan HIV Melalui Seks Bebas Di Usia Remaja Akhir Berbasis Ilustrasi Digital Guna Memberikan Kesadaran Bahaya Penularan Virus HIV - Nugroho, Bramantya; Budiardjo, Hardman; Hidayat, Wahyu (Jurnal Art Nouveau, 2016)
Many people mistakenly think that HIV equals AIDS. This is because both of these are often used interchangeably to describe the disease. More specifically, HIV is a virus, while AIDS is a condition. Sexual promiscuity among teenagers already occupies presentation alarming. One cause of infections in adolescents is their lack of knowledge regarding HIV and AIDS. It is unfortunate if a teenager suffering from AIDS, it affects the level and quality of human resources in Indonesia. because the average person with AIDS always lead to death, it reduces the population. Moreover, adolescents are the young generation successor to the nation, it is very unfortunate if the younger generation which is expected to be the bearer of a better future for themselves and the State, should be wasted in vain simply because of a virus and the disease. Associated with the lifestyle of today's youth, in addition to educational programs and seminars on campus locations, it is time to strengthen the network of information on education against HIV with other media. One of them could be through a hobby teens, like social networks, or reading books. Talk about the books, the teenagers would know the terms of comics, either in book form or online version that is currently popular among teenagers. Media comics is a medium that has the properties of simple, clear, easy to understand and more personalized so that is informative and educative. Designing a comic book about the transmission of hiv through free sex in their late teens-based digital illustration to bring awareness to the danger of transmission of HIV, will talk about the HIV / AIDS virus in a teenager's life end with life in the sex and the threat of HIV transmission along with the type of the type of transmission. Digital techniques also began frequently used by comic artists around the world, but some were still using traditional means. Even so, the results are processed through a digital technique is no less great in the traditional way. There are techniques that can not be done by hand, but the feature is available when it is done with digital techniques. With the comic book about the transmission of hiv through free sex in their late teens-based digital illustration to bring awareness to the danger of transmission of HIV, hopefully will be able to give an understanding of HIV / AIDS both how it is transmitted and the media, as well as knowledge of how to prevent and be careful not happen again increased cases of HIV / AIDS victims in their teens.Keywords: Comic Books, Digital, HIV, AIDS, Youth, sex, Awareness transmission.